Unveiling recurrent jets of the ULX Holmberg II X-1: evidence for a massive stellar-mass black hole? - Cseh, D.; Kaaret, P.; Corbel, S.; Grisé, F.; Lang, C.; Kording, E.; Falcke, H.; Jonker, P.; Miller-Jones, James; Farrell, S.; Yang, Y.; Paragi, Z.; et al. (Oxford University Press, 2014)
We report on the discovery of an apparent triple radio structure hidden inside the radio bubble of the ultraluminous X-ray source Holmberg II X-1. The morphology is consistent with a collimated jet structure, which is observed to emit optically thin synchrotron radiation. The central component has a steep radio spectrum and is brighter than the outer components indicating a renewed radio activity. We estimate a minimum time-averaged jet power of ~2 × 10^39 erg s-1 that is associated with a time-averaged isotropic X-ray luminosity of at least 4 × 10^39 erg s-1. Our results suggest that Holmberg II X-1 is powered by a black hole of MBH = 25 M☉, that is inferred to be accreting at a high Eddington rate with intermittent radio activity.